On training targets for noise-robust voice activity detection - Braun, Sebastian; Tashev, Ivan (European Signal Processing Conference (EUSIPCO), 2021)
The task of voice activity detection (VAD) is an often required module in various speech processing, analysis and classiﬁcation tasks. While state-of-the-art neural network based VADs can achieve great results, they often exceed computational budgets and real-time operating requirements. In this work, we propose a computationally efﬁcient real-time VAD network that achieves state-of-the-art results on several public real recording datasets. We investigate different training targets for the VAD and show that using the segmental voice-to-noise ratio (VNR) is a better and more noise-robust training target than the clean speech level based VAD. We also show that multi-target training improves the performance further.